Taking the grading leniency story to the edge. The influence of student, teacher, and course characteristics on student evaluations of teaching in higher education - Brockx, Bert; Spooren, Pieter; Mortelmans, Dimitri (Educational assessment, evaluation and accountability, 2011)
The use of student evaluation of teaching (SET) to evaluate and improve teaching is widespread amongst institutions of higher education. Many authors have searched for a conclusive understanding about the influence of student, course, and teacher characteristics on SET. One hotly debated discussion concerns the interpretation of the positive and statistically significant relationship that has been found between course grades and SET scores. In addition to reviewing the literature, the main purpose of the present study is to examine the influence of course grades and other characteristics of students, courses, and teachers on SET. Data from 1244 evaluations were collected using the SET-37 instrument and analyzed by means of cross-classified multilevel models. The results show positive significant relationships between course grades, class attendance, the examination period in which students receive their highest course grades, and the SET score. These relationships, however, are subject to different interpretations. Future research should focus on providing a definitive and empirically supported interpretation for these relationships. In the absence of such an interpretation, it will remain unclear whether these relationships offer proof of the validity of SET or whether they are a biasing factor.